MTHFR C677T polymorphism and risk of nonsyndromic cleft lip with or without cleft palate in the Moroccan population - Rafik A (The Application of Clinical Genetics, 2019)
Amine Rafik,1,2 Laila Rachad,2 Abdou-samad Kone,2 Sellama Nadifi2 1Department of Plastic Surgery, Alfarbi Hospital, Oujda, Morocco; 2Laboratory of Medical Genetics and Molecular Pathology, Faculty of Medicine and Pharmacy Casablanca, University Hassan II, Casablanca, Morocco Background: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common craniofacial malformations observed. Several studies suggest that the decrease in folate has been associated with a higher risk of NSCL/P. The present study aimed to determine the association of 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism gene with the occurrence of NSCL/P in the Moroccan population.Methods: MTHFR C677T was genotyped in 52 Moroccan patients and 182 unrelated controls, using a PCR followed by restriction fragment length polymorphism.Results: The results of the study revealed a genotypic and phenotypic distribution in equilibrium with Hardy–Weinberg’s law (χ2=0.36, P=0.55). The frequency of heterozygous genotype C/T and the T allele in controls and patients were 40.7% vs 15.4% and 26%, respectively.Conclusion: A low association was found between the C677T polymorphism of the MTHFR gene and a risk for the development of NSCL/P in the Moroccan population (OR =0.24, P=0.0005). Keywords: MTHFR, cleft lip and palate, C677T polymorphism, PCR, RFLP